Investigating perceptions of reliability, efficiency and feasibility of data storage technology: A case study of cloud storage adoption at UCT Faculty of Science - Netshiongolwe, Mpho (Library and Information Studies Centre (LISC), 2020)
Within an increasing number of organisations cloud storage is becoming more common as large amounts of data from people and projects are being produced, exchanged and stored (Chang & Wills, 2016: 56). In fact, “technology has evolved and has allowed increasingly large and efficient data storage, which in turn has allowed increasingly sophisticated ways to use it (Staff, 2016: n.p.). Thus, the aim of this study is to investigate the perceptions of reliability, efficiency and feasibility of data storage technology. The investigation is done by addressing claims and perceptions of data storage technology within the Faculty of Science at UCT. This study intends to determine if cloud storage is the future of storing, managing and preservation of digital data. The study used a qualitative research method grounded by Management Fashion Theory. Data was collected from three case studies from the Faculty of Science, and also from a desktop internet search on the marketing of cloud storage. Data collection from the case studies was facilitated through semi-structured interviews and from three researchers and academics who are working on cloud storage projects. Main themes that guided the dialogue during data collection originated from reviewed literature. The study concludes that cloud storage is the way forward for storing, sharing and managing research data. Academic researchers find storing data on cloud beneficial; however, it comes with challenges such as costs, security, access, privacy, control and ethics.